"My life disappeared in illness": bipolar disorder and themes in narrative identity. Issue 7 (9th August 2022) - Pedersen, Anne Mai; Straarup, Krista Nielsen; Thomsen, Dorthe Kirkegaard
ABSTRACT: Bipolar Disorder (BD) has substantial consequences for the course of life and the formation of self and identity. In the present study, we extended the existing literature by examining narrative identity. Fifteen female outpatients with remitted BD and fifteen non-clinical control participants described past and future chapters in their life stories. The chapters were coded for agency, communion, redemption and contamination. Patients diagnosed with BD described their past chapters with lower agency, lower communion and more contamination compared to the control group. Contrary to our expectations, the future chapters described by the BD patients did not differ significantly from the control group. A focus on narrative identity may contribute to understanding the disorder and inspire interventions targeting personal recovery.